ANFIS-Based Power Quality Enhancement and Harmonic Reduction in Hybrid Solar Wind Grid Systems - NANAPURAM CHANDRASHEAKR; V.V. GAYATHRI; Dr. K. SUDARSAN (Utilitas Mathematica, 2025)
This paper presents an intelligent control-based enhancement of a hybrid solar photovoltaic (PV) and wind energy system integrated into the power grid. The study extends a previously developed MATLAB/Simulink model for hybrid renewable energy integration by incorporating an Adaptive Neuro-Fuzzy Inference System (ANFIS) controller to improve dynamic response and minimize Total Harmonic Distortion (THD). The proposed ANFIS controller effectively manages nonlinearity and parameter uncertainty, ensuring stable DC-link voltage and improved power factor during variable solar irradiation and wind speed conditions. Comparative performance analysis with conventional PI and Fuzzy controllers demonstrates that the ANFIS-based model yields smoother voltage and current waveforms, enhanced transient stability, and significant harmonic reduction. Simulation results confirm that the proposed approach achieves lower THD and superior voltage regulation, thus ensuring reliable power delivery to the grid. This intelligent hybrid renewable energy integration scheme contributes toward developing more efficient, adaptive, and sustainable power systems suitable for modern smart grids.